Endodontic status and retention of molars in periodontally treated patients: results after 10 or more years of supportive periodontal therapy - Pretzl, Bernadette; Eickholz, Peter; Saure, Daniel; Pfefferle, Thorsten; Zeidler, Anna-Kristina; Dannewitz, Bettina (Journal of clinical periodontology, 2016)
Objectives:to assess the influence of endodontic status on retention of molars in patients under supportive periodontal treatment (SPT). Material & Methods:a total of 136 subjects with 1015 molars at baseline were examined retrospectively, including 188 endodontically treated molars in 90 patients. Multilevel Cox regression analysis identified factors contributing to loss of molars. Results: root canal treatments contributed significantly to loss of molars during on average 13.2 years of SPT (Hazard ratio: 2.98, 95% CI: 1.74-5.1, p < 0.001). Endodontic treatment was more frequently present in first molars (p < 0.001) and in the maxilla (p = 0.01). In endodontically treated molars, degree III furcation involvement could be detected more often compared to molars without root canal treatment (p < 0.001). Among the root canal-treated molars, several patient and tooth-related factors showed an impact on tooth retention, but only molars with a periapical index of 4 and 5 (labelled “diseased”) were significantly more often lost.Conclusion:the retention of molars in periodontally compromised patients after periodontal treatment is influenced by periodontal as well as endodontal factors. On a long-term basis, it is feasible to retain these teeth via active periodontal treatment and SPT for more than 10 years.